O primeiro banho do recém-nascido : intervenção da enfermagem obstétrica no alojamento conjunto - Lima, Rosana Oliveira de (2018)
The first bath of the newborn constitutes a very important moment for the family, providing less pain stimulation, crying, improving the length and quality of sleep, and reducing the mother's anxiety levels. Objective: To evaluate the effects of the Nursing intervention-first bath in the behavioral parameters of the newborn; to evaluate the effecgts of the Nursing intervention-first bath of the newborn in the levels of anxiety of the mother; and to develop didactical material about the Nursing intervention-first bath of the newborn at the joint accomodation of the Maternity of the University Hospital Cassiano Antônio de Morais in Vitoria, ES. Method: This is a controlled randomized clinical trial with a sample of 33 newborn babies, randomized in control and intervention groups, hospitalized at a joint accommodation in a teaching hospital. The technique of interview with registry on a form, Trace-State Anxiety Inventory, and a questionnaire for the physical evaluation of the baby were used for data collection. Presence of crying, time of sleep after the newborn’s bath, and maternal anxiety were defined as dependent variables. The Nursing Intervention-First Bath was defined as an independent variable. The control variables related to the newborn were: pregnancy age; weight at birth; weight before the bath; weight loss; room temperature; water temperature; time of bath and time of body care. Those related to the mother: origin; age; place and education. Before the newborn’s intervention-first bath, the environment and the newborn were prepared. After that, the eight stages that compose the intervention-first bath were performed in the newborns of the intervention group. The control group received the bath according to the institution’s routine. SPSS-version 24 was used for statistical analysis. The characterization of data was done through observed frequency, percentage, central trend analysis and variability. Significance level of 5% was adopted, with a trust interval of 95%. Fisher’s exact test was used to assess the association between the newborn groups in regard to crying during bath, and time of sleep. Student T test was used for paired samples, and the average clinical data of the groups was compared. Results: Crying during the bath was perceived in 93.33% of the newborns in the control group, while in the intervention group that proportion was of 55.56%. 60.00% of the newborns in the control group slept 120 minutes, and 77.78% of those in the intervention group slept 180 minutes. Anxiety score beofre the intervention-first bath of the newborn (30.5; DP ± 7.0) was larger than the one after the intervention (27.3; DP ± 5.3). Conclusion: The Nursing intervention-first bath of the newborn showed significant data in the comparison between the control and intervention groups relating to crying, time of sleep, and in the mother's levels of anxiety. This practice should be incorporated to the activities of the nurse for the binomial at the joint accomodation. The study has enabled the production of an illustrative folder with the description of all stages of the first bath to facilitate the mother's internalization of this care.